Bloom's Taxonomy and It’s Application in USIM's iNaQ Model - Mahyuddin Hashim; Noornajihan Ja‘afar; Nurul Asiah Fasehah Muhamad; Adnan Mohamed Yusoff; Norakyairee Mohd. Raus; Ahmad Sanusi Azmi (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
Indexed by SCOPUS